A. 2746-C: WHAT OTHER ORGANIZATIONS HAVE TO SAY ABOUT IT (Tufts Archival Research Center, 2007)
List of comments made by organizations in opposition to the proposed ban on smoking in public places in New York State. Provides sound bites to be used in media campaigns and facts for grass roots lobbying. Cites the onerous nature of restrictions and impracticality of implementing ban, as well as the potentially devastating economic impact.